2014
DOI: 10.1158/0008-5472.can-14-1784
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Modulation of Estrogen-Induced Apoptosis by Synthetic Progestins in Hormone Replacement Therapy: An Insight into the Women's Health Initiative Study

Abstract: Hormone replacement therapy (HRT) is widely used to manage menopausal symptoms in women, and can comprise an estrogen alone or an estrogen combined with a progestin. The Women’s Health Initiative demonstrated in their randomized trials that estrogen alone HRT decreases the risk of breast cancer in post-menopausal women, while combined estrogen plus a progestin (medroxyprogesterone acetate, MPA) HRT increases this risk. Long-term estrogen-deprived MCF-7:5C cells were used to model the post-menopausal breast can… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 35 publications
0
40
0
Order By: Relevance
“…Indeed a high dose of MPA used as a breast cancer therapy or as a depot injection for contraception, causes weight gain as a glucocorticoid type side effect. The glucocorticoid and progestin activating of synthetic progestins is recognised in the laboratory and recent study (181) addressed the hypothesis that the glucocorticoid properties of MPA could influence and modulate the apoptotic actions of estradiol in LTED breast cancer cells.…”
Section: Glucocorticoid Activity and Apoptosismentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed a high dose of MPA used as a breast cancer therapy or as a depot injection for contraception, causes weight gain as a glucocorticoid type side effect. The glucocorticoid and progestin activating of synthetic progestins is recognised in the laboratory and recent study (181) addressed the hypothesis that the glucocorticoid properties of MPA could influence and modulate the apoptotic actions of estradiol in LTED breast cancer cells.…”
Section: Glucocorticoid Activity and Apoptosismentioning
confidence: 99%
“…However these clues that MPA might modulate estrogen-induced apoptosis over time and create new cell populations that grow into tumours, is an important finding: MPA could select for surviving breast cancers by modulating estrogen-induced apoptosis over years of therapy in women who are a decade or more from menopause as documented in the WHI (138). Laboratory evidence for modifying apoptosis by estrogen through the glucocorticoid action of MPA was presented by Sweeney et al (181). This new finding coupled with the knowledge that rapid plasticity of hormone resistance occurs as a response to selection pressure (172, 175177), suggest a fundamental principle has now emerged based on selection pressure over years in patients..…”
Section: Glucocorticoid Activity and Apoptosismentioning
confidence: 99%
“…Laboratory findings that re-transplantation of tamoxifen-stimulated tumors into successive generations of athymic mice over 5 years results in the selection of a resistant tumor cell population that is killed by physiological levels of E 2 (2, 3), has resulted in the new biology of E 2 -induced apoptosis (47). Indeed, E 2 -induced apoptosis has been used successfully to treat breast cancer after the failure of AI therapy (8) and to explain the action of E 2 replacement therapy for postmenopausal women in their 60s having a lower incidence of breast cancer and mortality (9, 10). The laboratory and clinical data describing the effects of estrogens to cause tumor cell death and tumor regression have been linked to E 2 -induced apoptosis in vulnerable cell populations created by selection pressure in long term E 2 -deprived environments (11).…”
Section: Introductionmentioning
confidence: 99%
“…Sweeney et al identified a potential role for GR in breast cancer pathogenesis by studying MPAs effect on breast cancer cells as compared to that of dexamethasone (Dex) and norethindrone acetate (NETA). 19 Like Dex, MPA blocked E2-induced apoptosis, allowing for continued proliferation of these cells. In addition, like Dex, MPA blocked E2-induced genes related to apoptosis.…”
Section: Breast Cancer Cells: Studies In Vitromentioning
confidence: 96%
“…Sweeney et al found that MPA combined with E2 stimulated proliferation in long-term estrogen deprived MCF-7 (MCF-7:5C) cells, while E2 alone resulted in cell death. 19 …”
Section: Breast Cancer Cells: Studies In Vitromentioning
confidence: 99%